Leadership styles and job satisfaction - Soo Foon, Moey (IIUM Press, International Islamic University Malaysia, 2017)
the study was conducted to find out the main factors contributing to the above matter. As nursing education increases its complexity, good leadership and effective educators are vital for greater college performance and better student achievement. Studying effective leadership styles and applying them in the nursing faculty can be beneficial to job satisfaction which can aid in augmenting nursing education. This book seeks to ascertain the causal relationship between the Malaysian nursing academic leadership styles and the moderating effect of demographic factors on nurse educators’ job satisfaction.